PEMMALI: METODE DAKWAH LELUHUR BUGIS MAKASSAR - ZAENAL ABIDIN; SABRI SAMIN; MOH SABRI AR (Fakultas Dakwah dan Komunikasi, 2019)
This article examines the pemmali as a method of da'wah by Bugis and Makassar ancestors in maintaining the noble values formulated in the cultural system. This study with the dawah approach found that the Bugis and Makassar people always maintained the most fundamental values, namely siri'. This value is at the core of a cultural system called pangadereng. Implementation of Pangangadereng is always maintained and controlled through paseng (warning / tazkirah) or (message / wasiyah) and pemmali or prohibition and prevention. Paseng has a role in directing the implementation of the values of Pangangadereng, while pemmali as an effort to prevent violations against pangngadereng. Paseng in the science of da'wah aims to amar ma'ruf, while pemmali is directed at the nahi munkar. Amar ma'ruf and nahi munkar in the science of da'wah are part of the function of dakwah activities that must be realized. There are various ways of carrying out these functions, including the tanzīr methods. The tanzīr which means a warning against this threat was taken by the ancestors of the Bugis and Makassar people with pemmali